Pediatric strokes: A hospital based observation - Ganesh, Ramaswamy; Deenadayalan, Munirathinam; Janakiraman, Lalitha; Viswanathan, Venkataraman (Journal of Pediatric Neurology, 2006)
Childhood strokes are not so rare as once thought and its incidence is equal to pediatric brain tumors. The recent advent of more accurate diagnostic techniques has lead to a surge of interest, which may lead in the near future to strategies for treatment and prevention. We retrospectively analyzed the prevalence of first episode of arterial stroke in children. This study was conducted in a private tertiary care hospital for children from June 2002 to May 2004 involving 12 children with first episode of arterial stroke out of 23,125 admissions. Majority (42%) of the children was between 1 month and 5 years and hemiplegia/hemiparesis was the common clinical presentation. Ten children had infarct and two had hemorrhage. The causes identified after detailed investigations were tetralogy of Fallot (2), protein C deficiency (1), homocystinuria (1), nonspecific vasculitis (1), hypercholesterolemia (1), factor XIII deficiency (1), late hemorrhagic disease of the newborn (1) and idiopathic (4). All the children recovered though some had neurological deficit and there was no mortality. Ischemic stroke was more common than hemorrhagic stroke. Prognosis of pediatric stroke is good and the treatment is largely supportive.
Keywords: Stroke; ischemia; hemorrhage; CT; MRI